Evaluation of APRIL in serum of patients with Hashimoto’s Thyroiditis - Santos, Adriana Carvalho (2021)
Hashimoto’s thyroiditis (HT) is an autoimmune and inflammatory disease in which antibodies are directed against the thyroid gland leading to chronic inflammation and hypothyroidism. The autoimmunity against thyroid antigens can be associated to genetic background and environmental factors. Thyroid peroxidase (TPO) and thyroglobulin (TG) are the major autoantigens for characterizing the disease. HT is related to the activation of autoreactive CD4+ T cells, CD8+ cytotoxic T cells and antithyroid antibody producing-B cells. Among several cytokines related to the pathogenesis of HT, a proliferation-inducing ligand (APRIL) has been studied in the context of the establishment and/or maintenance of autoimmune diseases. The role of APRIL in the pathogenesis of HT is still poorly understood. Therefore, the present study aimed to compare APRIL serum concentration in HT patients and healthy donors by ELISA. We observed a significant decrease in APRIL concentration in HT patients when compared to the control group, and a positive correlation between APRIL level and age. Our results suggest that the APRIL molecule can compose the cytokine profile along the inflammatory response in HT, however, other investigations should be proposed to understand its molecular mechanisms via specific receptors and other regulatory loops.